FRI0341 Anti-Carp Antibodies in Two Large Cohorts of Patients with Rheumatoid Arthritis and their Relationship to Genetic Risk Factors, Cigarette Smoking and Other Autoantibodies. (10th June 2014) - Jiang, X.; Trouw, L.; van Wesemael, T.; Shi, J.; Bengtsson, C.; Kallberg, H.; Malmstrom, V.; Israelsson, L.; Hreggvidsdottir, H.; Verduyn, W.; Klareskog, L.; Alfredsson, L.; et al.
Abstract : Background: In rheumatoid arthritis (RA), several genetic risk factors and smoking are strongly associated with the presence of anti-citrullinated protein antibodies (ACPA), while much less is known about risk factors for ACPA-negative RA. Antibodies against carbamylated proteins (anti-CarP) have been described in both ACPA-positive and ACPA-negative RA patients. Objectives: In this study we have analysed the relationships between anti-CarP antibodies, ACPA, genetic risk factors ( HLA-DRB1 alleles and PTPN22 ) and smoking in RA. Methods: Presence of antibodies to carbamylated fetal calf serum (CarP-FCS) and fibrinogen (CarP-Fib) was determined by in-house ELISAs in the Leiden Early Arthritis Cohort (EAC) and in the Swedish Epidemiological Investigation of RA (EIRA) cohort. Odds ratios for associations with different HLA-DRB1 alleles, PTPN22 genotypes and smoking were calculated separately for each cohort as well as in the combined meta-analysis, in RA subsets defined by anti-CarP and anti-cyclic citrullinated peptide (CCP) antibody status. Results: In both cohorts, anti-CarP antibodies were mainly detected in the anti-CCP-positive population, but also in the anti-CCP-negative population. No associations between anti-CarP antibodies and HLA-DRB1 shared epitope alleles could be identified, while a consistent signal for an association between anti-CarP-FCS and HLA-DRB1* 03 was observed. Further analyses did not reveal any specific associations of anti-CarP antibodies with other HLA-DRB1 alleles, PTPN22 genotypes or smoking. Conclusions: Anti-CarP antibodies were present in both ACPA-positive and ACPA-negative RA. Except for a modest association with HLA-DRB1* 03, there were no strong associations between anti-CarP antibodies and HLA-DRB1 alleles, PTPN22 or smoking. These data suggest that different biological mechanisms may underlie anti-CarP versus anti-CCP antibody formation. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4653